Crop production : principles and practices - Metcalfe, Darrel S.; Elkins, Donald M.; Hughes, Harold De Mott (New York : Macmillan, 1980)
The book is divided into six Chapters: 1. History and current status of crops. 2. Environmental factors affecting crop production. 3. Botany of crop plants. 4. Crop production practices. 5. Field crops. 6. Forage crops
First-2d ed. by H. D. Hughes and E. R. Henson; 3d ed. by H. D. Hughes and D. S. Metcalfe.
Includes bibliographical references and index.
rpm 24/01/2019
Loans
Keywords: Field crops